Contruction of the Meaning of the Song Imagine Jhon Lennon’s as a Media for Social Critism Communication for John Lennon Fans - Andriani, Astri Dwi; Sadikin, Dera Maharani (MultiTech Publisher, 2024)
This research is entitled